EFL teachers’ student-centered pedagogy and assessment practices: challenges and solutions - Nazim, Mohd; Alzubi, Ali Abbas Falah; Fakih, Abdul-Hafeed (Journal of Education and Learning (EduLearn), 2024)
The fact that English teachers encounter challenges while employing student-centered pedagogy and assessment practices is beyond argument. Empirical evidence indicates that, particularly in the context of Najran University, relatively little attention has been paid to researching the issue and offering solutions to coping with it. Consequently, this study examined English as a foreign language (EFL) teachers’ employment of student-centered pedagogy and assessment practices in the Saudi EFL context concerning execution, challenges, and solutions. Also, it correlated the respondents’ answers with their gender, experience, degree, and specialization. The descriptive survey design was used to achieve the study objectives. The study tools, a questionnaire and a semi-structured interview were applied to a convenient sample of (73) faculty members. The results showed that the study sample highly employs pedagogy and assessment practices focused on students. In addition, the demographic variables of gender, experience, degree, and specialization did not have any significant role in affecting the responses to employing pedagogy and assessment practices. Finally, the content analysis of the semi-structured interview revealed the challenges and solutions to employing pedagogy and assessment practices. In light of the current results, the researchers proposed recommendations and implications.